2016
DOI: 10.3390/ijerph13060544
|View full text |Cite
|
Sign up to set email alerts
|

BMI and BMD: The Potential Interplay between Obesity and Bone Fragility

Abstract: Recent evidence demonstrating an increased fracture risk among obese individuals suggests that adipose tissue may negatively impact bone health, challenging the traditional paradigm of fat mass playing a protective role towards bone health. White adipose tissue, far from being a mere energy depot, is a dynamic tissue actively implicated in metabolic reactions, and in fact secretes several hormones called adipokines and inflammatory factors that may in turn promote bone resorption. More specifically, Visceral A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
121
2
8

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(140 citation statements)
references
References 237 publications
(245 reference statements)
9
121
2
8
Order By: Relevance
“…Although the results were sometimes controversial, many epidemiological studies have reported that postmenopausal women with higher BMI had a reduced risk for hip or pelvis fracture (DiPietro et al, 1993, Gnudi et al, 2009, Prieto-Alhambra et al, 2012, Sogaard et al, 2015). However, it was estimated that, for obese populations, there is a U-shape relationship between BMI and fracture risk and that the protective effects of weight on bone are reduced along with the increment of BMI (Palermo et al, 2016). The PTH was elevated in the obese women, which might damage the bone architecture and reduce the BMD values (Goldner et al, 2008, Bolland et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the results were sometimes controversial, many epidemiological studies have reported that postmenopausal women with higher BMI had a reduced risk for hip or pelvis fracture (DiPietro et al, 1993, Gnudi et al, 2009, Prieto-Alhambra et al, 2012, Sogaard et al, 2015). However, it was estimated that, for obese populations, there is a U-shape relationship between BMI and fracture risk and that the protective effects of weight on bone are reduced along with the increment of BMI (Palermo et al, 2016). The PTH was elevated in the obese women, which might damage the bone architecture and reduce the BMD values (Goldner et al, 2008, Bolland et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The PTH was elevated in the obese women, which might damage the bone architecture and reduce the BMD values (Goldner et al, 2008, Bolland et al, 2006). The inflammation factors and adipokines secreted from the white adipose tissue could stimulate bone resorption, and abdominal/visceral obesity is usually associated with lower BMD values (Palermo et al, 2016). Moreover, a higher BMI is associated with the reduced bioavailability of 25(OH)D (Wortsman et al, 2000, Vimaleswaran et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to storing energy, it is also an active endocrine organ that modulates adipokine (e.g., leptin, resistin, adiponectin) and inflammatory cytokine (e.g., TNFα, IL-6, TGF-β) release, 21 affecting both local and systemic environments. Fat tissue plays a role in a range of physiological processes, including immune function, 22 glucose homeostasis, 23 and energy balance.…”
Section: Impact Of Obesity On Musculoskeletal Tissue Systemsmentioning
confidence: 99%
“…A obesidade pode ser definida como uma desordem metabólica complexa envolvendo um acúmulo anormal ou excessivo de gordura corporal (Palermo et al, 2016). Dados da Organização Mundial de Saúde (OMS) mostram que em 2014 mais de 1,9 bilhões de adultos podiam ser classificados como sobrepeso e, desses, mais de 600 milhões eram obesos, correspondendo a 13% da população adulta mundial (Palermo et al, 2016;WHO, 2016 (Pisani et al, 2016).…”
Section: Methodsunclassified
“…Dados da Organização Mundial de Saúde (OMS) mostram que em 2014 mais de 1,9 bilhões de adultos podiam ser classificados como sobrepeso e, desses, mais de 600 milhões eram obesos, correspondendo a 13% da população adulta mundial (Palermo et al, 2016;WHO, 2016 (Pisani et al, 2016).…”
Section: Methodsunclassified